Kontribusi Kompetensi Pedagogik, Kompetensi Profesional dan Motivasi Kerja terhadap Kinerja Guru Penjasorkes SMP di Kabupaten Pati - Salmawati, Salmawati; Rahayu, Tandiyo; Lestari, Wahyu (Journal of Physical Education and Sports, 2017)
Tujuan Penelitian untuk menganalisis seberapa besar kontribusi kompetensi pedagogik, kompetensi profesional dan motivasi kerja terhadap kinerja guru penjasorkes SMP Negeri di Kabupaten Pati. Penelitian kuantitatif menggunakan 3x1 factor design. Analisis data menggunakan korelasi regresi. Hasil penelitian: (1) Kontribusi kompetensi pedagogik terhadap kinerja guru sebesar 6,9%, (2) Ada kontribusi kompetensi profesional terhadap kinerja guru sebesar 30,23%. (3) Ada kontribusi motivasi kerja terhadap kinerja guru sebesar 7,8%. (4) Ada kontribusi positif antara kompetensi pedagogik dan kompetensi profesional dengan kontribusi sebesar 13,9%. (5) Ada kontribusi positif antara kompetensi Pedagogik dan motivasi kerja dengan kontribusi sebesar 11,3%. (7) Ada kontribusi antara kompetensi pedagogik, kompetensi profesional dan motivasi kerja secara bersama-sama terhadap kinerja guru dengan kontribusi sebesar 15,4%. Simpulan penelitian: Kompetensi pedagogik, kompetensi profesional dan motivasi kerja berkontribusi terhadap kinerja guru penjasorkes SMP Negeri di Kabupaten Pati.The research to analyze the contribution of pedagogic competence, professional competence and motivation to work on teacher performance of of Physical Education and Health Teachers Junior High School in Pati regency. Quantitative research using 3x1 factor design. Analysis of data using regression correlation. Results of the study: (1) Contribution of pedagogical competence of the teacher's performance by 6.9%. (2) There is the contribution of professional competence on teachers performance of 30.23%. (3) There is a contribution of work motivation on teachers performance of 7.8%., (4) There is a positive contribution between pedagogical competence and professional competence with a contribution of 13.9%. (5) There is a positive contribution between Pedagogic competencies and motivation to work with a contribution of 11.3%. (6) There is a contribution between professional competence and motivation to work with a contribution of 12.5%. (7) There is a contribution between pedagogical, professional competence and motivation to work together on teachers performance with a contribution of 15.4% . The conclusions of the study: pedagogical competence, professional competence and motivation to contribute to teachers performance of Physical Education and Health Teachers Junior High School in Pati regency.